2017
DOI: 10.1155/2017/3059159
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Adaptive Template Size Pixel-Tracking Method for Monitoring Large-Gradient Mining Subsidence

Abstract: The monitoring of large-gradient deformation caused by coal mining is of great significance to the prevention and management of disasters in mining areas. The interferometric synthetic aperture radar (InSAR) method captures the small-gradient ground deformation on the edge of the subsidence basin accurately but is unreliable for capturing large-gradient deformation. The intensitybased pixel-tracking method (e.g., the normalized cross-correlation (NCC) method) can overcome the limitations of InSAR's maximum det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The searching patterns are detected on the basis of values of accumulated votes higher than the predefined threshold value. The Hough transform [ 20 ] together with methods based on the convolution of the image with a bank of circular wavelets [ 12 ], template recognition [ 21 ], or deep convolutional neural network [ 22 ] were used for the deformation patterns detection in the SAR interferograms. None of them proved to be capable of the reliable detection of irregular circular fringes on the noisy SAR interferograms.…”
Section: Introductionmentioning
confidence: 99%
“…The searching patterns are detected on the basis of values of accumulated votes higher than the predefined threshold value. The Hough transform [ 20 ] together with methods based on the convolution of the image with a bank of circular wavelets [ 12 ], template recognition [ 21 ], or deep convolutional neural network [ 22 ] were used for the deformation patterns detection in the SAR interferograms. None of them proved to be capable of the reliable detection of irregular circular fringes on the noisy SAR interferograms.…”
Section: Introductionmentioning
confidence: 99%
“…InSAR technique has been applied to monitor the land subsidence in coal mining area [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Ji et al [18] demonstrated InSAR's ability to cost-effectively monitor illegal mining activities.…”
Section: Introductionmentioning
confidence: 99%
“…Literature research shows that there are mainly two types of approaches to solve the problems of full-scale gradient mining subsidence D-InSAR monitoring. The first method is single pass OT(Offset Tracking) / (InSAR and OT) + prior model monitoring method [18]- [20]. On the basis of high resolution SAR image, it is firstly to get largegradient LOS deformation of mining subsidence basin by OT technology.…”
Section: Introductionmentioning
confidence: 99%